Kajian Literatur Pemanfaatan Media Digital dalam Mendukung Hasil Belajar PAI Peserta Didik MTs - Zidni Akholik Almaghfiroh (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
The development of digital technology has driven the transformation of Islamic Religious Education (PAI) learning to be more interactive and contextual. However, previous studies still show limitations, namely tending to be partial, focusing on the general effectiveness of digital media, and not comprehensively examining its impact on cognitive, affective, and psychomotor aspects in an integrated manner. Therefore, this study aims to analyze the use of digital media in supporting PAI learning outcomes, as well as identifying patterns and challenges in its implementation. This study uses a qualitative approach with a literature study type. Data were collected through searching scientific articles on Google Scholar and accredited journals for the period 2021–2025. Of the approximately 50 articles found, approximately 20 articles were selected based on criteria of relevance and methodological quality. Data analysis was conducted using content analysis techniques. The results of the study indicate that digital media contributes significantly to improving learning outcomes, especially in the cognitive aspect, while the affective and psychomotor aspects are contextual and depend on the learning design and the role of the teacher. The success of implementation is also influenced by the digital competence of educators, the availability of infrastructure, and institutional support. Thus, digital media is effective when pedagogically integrated into Islamic Religious Education (PAI) learning.